Design of an Automatic Solar Tracking System to Maximize Energy Extraction - Yadav, Sarvesh kumar; Mishra, Dhiraj Kumar; Shankar, Aditya; Kunar, Anuj (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
This paper presents the design of a solar tracking system driven by a mnicrochip PIC 18F452 micro controller. The system is based on two mechanisms. The first one is the search mechanism (PILOT) which locates the position of the sun. The second mechaniEsm(intelligent PANELS) aligns itself with the PILOT only if maximum energy possible could be extracted. On top of that the main advantage of the technique is that the rotation only takes place, if the energy obtained in the new position is higher then that consumed by the panels during the transition. So there are two mechanisms, one for the search which is mounted on a miniature motor and consumes only small amount of energy. Its role is to locate the best position for maximum energy extraction. The second one is the panels mechanism which rotates to the position when energy extraction is optimal.